L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

Représentation des femmes expertes en environnement dans les médias écrits québécois – Boutique - Réseau femmes et environnement (2022)
Les femmes expertes en environnement sont-elles sous-représentées dans les médias écrits québécois❓ C’est pour répondre à cette question que le Réseau des femmes en environnement a réalisé une étude exploratoire sur le sujet. Dans le cadre de cette étude : ➾ La littérature et les données récentes sur le sujet ont brièvement été explorées; ➾ 125 articles québécois tirés de la revue de presse produite par Copticom pour sa communauté de pratique en communication climatique ont été analysés ; ➾ Dix entrevues individuelles ont été menées auprès de journalistes et de femmes expertes souvent citées dans les médias relativement à des enjeux environnementaux ou de santé. Le Réseau a été accompagné dans cette démarche par Selma Vorobief, conseillère en évaluation participative et en recherche-action.
Keywords: 2000 à aujourd'hui; amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; discipline; environnement; médias; périodes historiques; québec; régions géographiques; santé; sciences; systèmes d'oppressions; thématiques; travail; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual health studies in gay and lesbian people: A critical review of the literature - Mijas, Magdalena; Grabski, Bartosz; Blukacz, Mateusz; Davies, London, UK, Dominic Pink Therapy (The Journal of Sexual Medicine, 2021)
Arrière-plan Le sujet de la santé sexuelle des gays et des lesbiennes semble être très peu étudié, au moins en partie en raison des limites générales inhérentes aux études sur la sexualité ainsi que des préjugés hétéronormatifs et des difficultés à atteindre ces populations. But Examiner de manière critique les études sur la santé sexuelle des gais et des lesbiennes afin d'identifier les lacunes et les préjugés existants dans la portée et la construction générale des recherches publiées. Méthodes L'ensemble de données comprenait 556 articles évalués par des pairs et identifiés grâce à la recherche Medline. Les caractéristiques clés des études ont été extraites selon le livre de codes développé pour cette étude et analysées de manière descriptive. Résultats Les résultats comprenaient : la méthodologie de recherche, la conception de l’étude, l’échantillonnage, le sujet de recherche et l’inclusion de la diversité dans les populations étudiées. Résultats La majorité des études étaient quantitatives (70,5 %), transversales (83,6 %) et utilisaient un échantillonnage de commodité (83,2 %). La plupart des articles portaient sur les comportements à risque en matière de VIH/IST, les vulnérabilités et la gestion des risques (26,3 %). Le sujet le moins souvent abordé concernait la fonction sexuelle des participants gais et lesbiennes plus âgés (0,5 %). Plus de 68 % des articles s'appuyaient sur des échantillons masculins et les études portant sur des échantillons exclusivement féminins en représentaient moins de 13 %. La plupart des études n'ont pas recruté de groupe d'âge spécifique (77,7 %) et incluaient des informations sur l'origine ethnique des participants à l'étude (62 %). Les informations sur l'éducation (58,7 %) ou d'autres indicateurs du statut socio-économique (52,8 %) étaient moins souvent déclarées. Traduction clinique Les limites méthodologiques des conceptions d'étude actuelles, des procédures d'échantillonnage et de la composition des échantillons, ainsi que de nombreuses zones d'omission limitent l'utilité clinique des recherches existantes. Points forts et Limites Cette étude offre un aperçu critique des défis les plus importants associés aux études sur la santé sexuelle des gais et des lesbiennes. La recherche dans la base de données Medline uniquement, l'inclusion exclusive d'articles rédigés en anglais et la portée limitée (sexualité gay et lesbienne uniquement) de la revue constituent les limites les plus importantes. Conclusions La santé sexuelle des gays et des lesbiennes est un domaine peu étudié, caractérisé par une concentration principale sur le VIH/IST et un manque de recherche de meilleure qualité incluant diverses sous-populations.
Keywords: approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; médecine; personnes gay; personnes lesbiennes; ressource en ligne; revue de la littérature; santé; santé sexuelle; sciences; systèmes d'oppressions; thématiques

Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Number: 5
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis

Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Section: 246 pages : tableaux, graphiques en couleur ; 28 cm
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. – From publisher's description. Contenu : Preface – Acknowledgements – About the author – The study of gender – Researching sex and gender – Gender stereotypes: masculinity and femininity – Hormones and chromosomes – Theories of gender development – Developing gender identity – Intelligence and cognitive abilities – Emotion – Relationships – Sexuality – School – Careers and work – Health and fitness – Stress, coping, and psychopathology – Treatment for mental disorders – How different? – References – Index.
Section: xix, 539 pages ; 26 cm
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

The vulva: Physiology and clinical management - Farage, Miranda A.; Maibach, Howard I. (CRC Press, 2017)
Compilation unique d'expertise sur l'anatomie, la physiologie, les questions cliniques et la recherche actuelle, ce manuel analyse la diversité des présentations en fonction de l'âge, de l'origine ethnique, des symptômes, des troubles, des diagnostics et de la toxicité. La deuxième édition de cette ressource essentielle pour toute personne prenant soin de patientes a été doublée pour inclure des chapitres supplémentaires. Tous les médecins, qu'ils soient dermatologues ou gynécologues, ainsi que ceux qui recherchent les preuves scientifiques et les symptômes, bénéficieront de l'expérience des contributeurs et éditeurs experts réunis ici.
Keywords: 2000 à aujourd'hui; corps; dermatologie; discipline; gynécologie; médecine; projet charge mentale; périodes historiques; santé; santé menstruelle; santé reproductive; santé sexuelle; sciences; sexualité; sexualité des femmes*; thématiques

Sex and gender considerations in transplant research: A scoping review - Laprise, Claudie; Cole, Katherine; Sridhar, Vikas Srinivasan; Marenah, Tida; Crimi, Cassandra; West, Lori; Foster, Bethany J.; Pilote, Louise; Sapir-Pichhadze, Ruth (Transplantation, 2017)
Background Despite the growing appreciation of the importance of sex and gender considerations in transplantation research, there is currently no framework or good practice guidelines for the appropriate handling of sex and gender issues in human allotransplantation research. Methods We will conduct a scoping review to synthesize the evidence on how matters of sex and gender have been handled in human allotransplantation research. We will survey the literature discussing sex and gender in relation to transplantation, including adult and pediatric patients, hematopoietic and solid organ transplant recipients as well as organ donors. We will search MEDLINE and Embase for literature discussing sex and gender in relation to transplantation. Two reviewers will independently evaluate the eligibility of all identified titles and abstracts for inclusion in the full text review, as well as data extraction. Descriptive data and information on how sex and gender have been considered in human transplantation research will be reported. Discussion This scoping review will be an important stepping stone towards the development of good practice guidelines on study design and analysis considerations when handling sex and gender issues in human transplantation research. This scoping review can also help identify methodological issues that restrict the translation of transplantation research findings into clinical practice related to underestimation of sex/gender differences. This review will ultimately identify major gaps, inform donor-recipient selection, guide personalized interventions, and prioritize research recommendations in human transplantation research. Electronic supplementary material The online version of this article (10.1186/s13643-017-0578-4) contains supplementary material, which is available to authorized users. Keywords: Sex, Gender, Transplantation, Scoping review
Keywords: 2000 à aujourd'hui; corps; discipline; médecine; projet charge mentale; périodes historiques; ressource en ligne; santé; sciences; thématiques; transplantation

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Prendre en compte le sexe et le genre dans le choix des situations à analyser : un enjeu pour l’intervention ergonomique - Laberge, Marie; Caroly, Sandrine (Perspectives interdisciplinaires sur le travail et la santé, 2016)
Le sexe/genre (s/g) doit être pris en compte dans le domaine de la santé au travail, puisque les hommes et les femmes n’occupent pas les mêmes emplois et ne sont pas exposés de la même façon aux risques de santé et sécurité au travail (SST). Cet article propose une réflexion sur les manières de considérer le s/g dans l’intervention ergonomique, en particulier lors des investigations préliminaires. Deux exemples issus d’interventions réalisées en France et au Québec sont présentés. Le premier exemple porte sur l’activité des médecins du travail dans la prévention des troubles musculosquelettiques (TMS). Le second traite du développement et de l’implantation d’une formation portant sur la SST. Dans les deux cas, ces questions portées par les ergonomes chercheuses ont permis de transformer la compréhension des dimensions liées aux parcours de santé, de travail et de vie personnelle pour que la prévention des lésions tienne compte des particularités des hommes et des femmes.
Keywords: amériques; discipline; ergonomie; europe; france; médecine; projet charge mentale; québec; ressource en ligne; régions géographiques; santé; santé au travail; sciences; thématiques; travail

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Gender matters in biological research and medical practice ∗ - Schiebinger, Londa; Stefanick, Marcia L. (Journal of the American College of Cardiology, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; corps; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; santé; sciences; thématiques

Why sex and gender matter in implementation research - Tannenbaum, Cara; Greaves, Lorraine; Graham, Ian D. (BMC Medical Research Methodology, 2016)
Arrière-plan Les organismes de financement de la recherche en santé et les rédacteurs de revues scientifiques ont récemment intensifié leurs efforts pour accroître la prise en compte des questions de sexe et de genre dans la conception, la conduite et la communication des études afin de garantir que les résultats de la recherche s’appliquent à tous. Cependant, l’examen de la littérature sur la recherche sur la mise en œuvre révèle que l’attention portée au sexe et au genre n’a pas encore infiltré les méthodes de recherche dans ce domaine. Discussion Les raisons pour lesquelles le sexe et le genre sont systématiquement pris en compte dans la recherche sur la mise en œuvre sont multiples. Le sexe et le genre sont importants dans la prise de décision, la communication, l’engagement des parties prenantes et les préférences pour l’adoption des interventions. Les rôles de genre, l’identité de genre, les relations de genre et le genre institutionnalisé influencent la manière dont une stratégie de mise en œuvre fonctionne, pour qui, dans quelles circonstances et pourquoi. De nouvelles preuves montrent que les théories des programmes peuvent fonctionner différemment au sein et entre les sexes, les genres et d’autres caractéristiques intersectionnelles dans diverses circonstances. En outre, sans une étude appropriée, les stratégies de mise en œuvre peuvent exploiter ou ignorer par inadvertance, plutôt que de transformer la réflexion sur le sexe et les facteurs liés au genre. Des techniques sont décrites pour mesurer et analyser le sexe et le genre dans la recherche sur la mise en œuvre en utilisant des méthodes à la fois quantitatives et qualitatives. Résumé Le présent article décrit l’application de méthodes d’intégration du sexe et du genre dans la recherche sur la mise en œuvre. Poser systématiquement des questions critiques sur le sexe et le genre conduira probablement à la découverte de résultats positifs, ainsi que de conséquences imprévues. Le résultat a le potentiel de renforcer à la fois la pratique et la science de la mise en œuvre, d’améliorer les résultats en matière de santé et de réduire les inégalités entre les sexes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; régions géographiques; santé; santé publique; sciences; thématiques; transfert des connaissances

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"–Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Queer Bioethic: Why its Time Has Come. - Wahlert, Lance; Fiester, Autumn (Bioethics, 2012)
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; care; corps; cours; discipline; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; santé; sciences; thématiques; éthique

Transidentité: de la théorie à la politique. Une métamorphose culturelle entre pragmatisme et transcendance - Espineira, Karine (L'information psychiatrique, 2011)
Du décret français du 10 février 2010 aux travaux de réécriture lancés par le DSM et la CIM, les questions transidentitaires doivent être discutées, appréhendées sur le plan théorique aussi bien que politique. Le schisme entre les associations d’usagers, les trans’ en demande et/ou en obligation de suivi, et les équipes hospitalières spécialisées dans la prise en charge de ce public, pour le cas de la France tout particulièrement, a une histoire intimement liée à un ordre présumé du social et de ses acteurs en termes de genre dans une vision binaire de la société. La demande de reconnaissance de savoirs, d’expertises du terrain transidentitaire s’est heurtée, dès le début des années 1980, au bouclier thérapeutique , que l’on peut définir comme l’argument ultime de l’instance médico-légale en charge du sujet transsexe, écartant les autres sujets/trajets trans’, pour mettre à distance toute intervention du politique, des sciences humaines et sociales dans ce qui est devenu un paradigme théorique : le changement de sexe est d’abord un changement culturel de genre. Enfin, l’instance médico-légale s’efforce d’ignorer sa propre politisation et militance. Partagé entre la volonté de résister et de participer face/avec un protocole inadapté, inefficace et culturellement obsolète, le terrain a connu ses propres mouvements s’interrogeant, s’interpellant sur l’esprit de la méthode. La question trans’ compte désormais autant de politiques que de groupes. La théorisation du fait trans’, trouve sa légitimité non pour revenir seulement sur l’inégalité homme/femme, mais pour lutter du même élan contre toute forme d’inégalité et de stigmatisation. Le terrain transidentitaire s’est profondément transformé, les outils pour l’appréhender comme le paradigme théorique lui-même, se doivent une chose : évoluer.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; militance; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; sociologie; thématiques; transféminisme; violences; violences médicales

Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

Butch/femme, F2M, pregnant man, tranny-boi: Gender issues in the lesbian community - Herbert, Sandra (Journal of Gay and Lesbian Mental Health, 2010)
The author discusses issues pertaining to transgender women and girls. Women identifying as male or transitioning to becoming male are often ignored in the scientific and lay literature on transgender people. The many newer terms for transgender women and girls are discussed, as well as new ways for transgender girls to express their identities. The importance of family and community supports is discussed, and common issues that young transgender people bring into mental health treatment are elucidated.
Keywords: amériques; discipline; identités LGBTQIA2+; médecine; personnes trans*; ressource en ligne; régions géographiques; santé; sciences; thématiques; états-unis

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

La procréation assistée, comment y voir clair? - Fédération du Québec pour le Planning des naissances (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; discipline; femmes*; maternité; médecine; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; sciences; thématiques

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques

The scientific revolution and the death of nature - Merchant, Carolyn (Isis, 2006)
The Death of Nature: Women, Ecology, and the Scientific Revolution, published in 1980, presented a view of the Scientific Revolution that challenged the hegemony of mechanistic science as a marker of progress. It argued that seventeenth-century science could be implicated in the ecological crisis, the domination of nature, and the devaluation of women in the production of scientific knowledge. This essay offers a twenty-five-year retrospective of the book’s contributions to ecofeminism, environmental history, and reassessments of the Scientific Revolution. It also responds to challenges to the argument that Francis Bacon’s rhetoric legitimated the control of nature. Although Bacon did not use terms such as “the torture of nature,” his followers, with some justification, interpreted his rhetoric in that light.
https://nature.berkeley.edu/departments/espm/env-hist/articles/84.pdf
Keywords: approches et analyses; capitalisme; discipline; environnement; projet charge mentale; santé; santé de la nature; sciences; sciences de l'environnement; sexisme; systèmes d'oppressions; thématiques; torture de la nature; violences; écoféminisme

Voices of South Asian Women: Immigration and Mental Health - Ahmad, Farah; Shik, Angela; Vanza, Reena; Cheung, Angela M.; George, Usha; Stewart, Donna E. (Women & Health, 2005)
Purpose: This qualitative research aimed to elicit experiences and beliefs of recent South Asian immigrant women about their major health concerns after immigration. Methods: Four focus groups were conducted with 24 Hindi-speaking women who had lived less than five years in Canada. The audiotaped data were transcribed, translated, and analyzed by identification of themes and subcategories. Results: Mental health (MH) emerged as an overarching health concern with three major themes, i.e., appraisal of the mental burden (extent and general susceptibility), stress-inducing factors, and coping strategies. Many participants agreed that MH did not become a concern to them until after immigration. Women discussed their compromised MH using verbal and symptomatic expressions. The stress-inducing factors identified by participants included loss of social support, economic uncertainties, downward social mobility, mechanistic lifestyle, barriers in accessing health services, and climatic and food changes. Women's major coping strategies included increased efforts to socialize, use of preventative health practices and self-awareness. Conclusion: Although participant women discussed a number of ways to deal with post-immigration stressors, the women's perceived compromised mental health reflects the inadequacy of their coping strategies and the available resources. Despite access to healthcare providers, women failed to identify healthcare encounters as opportunities to seek help and discuss their mental health concerns. Health and social care programs need to actively address the compromised mental health perceived by the studied group.
Keywords: amériques; asie; asie du sud; canada; charge mentale; cours; discipline; femmes immigrantes; médecine; régions géographiques; santé; sciences; soc1061; stress post immigration; thématiques

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis